Analisis Pendapatan Usahatani Tomat Dikelurahan Kaisabu Baru Kecamatan Sorawolio Kota Baubau - Wulandari, Fitri; Saediman, Saediman; Zani, Munirwan (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2019)
The results of this study showed that; (1) the amount of income  of the average tomato farming respondent for each planting season is Rp3.158.396; and the average income each hectare of  tomato farming for each planting season is Rp17.867.488; (2) with the efficiency of ratio R/C of Rp2,61, which means that if it is converted into hundreds of thousands meant that each expenditure is Rp100.000 the receip obtained is Rp261.000 and (3) the obstacles gained by the  farmers on tomato farming in abiotic factors are constraints of rain / weather, soil fertility is about 100% while flood and  irrigation factors reaches about 34,46%. For technology and agronomic factors, farming experiences constraints on low productivity with a percentage is 100% and there are no obstacles in cultivating tomatoes in other factors. Farming biotic factors have problems on pests and diseases offence which are 100%. On the other hand, on the socio economic factors of farming experienced obstacles to price and labor fluctuations which reaches 100%.